Penerapan Restorative Justice Dalam Penyelesaian Kasus Tindak Pidana Anak Di Bengkulu: Pendekatan Musyawarah Kekeluargaan Sebagai Solusi Hukum Anak - Sella Marenata; Salwa Haniyyah; Predi Alexander Sitorus (CV. ITTC INDONESIA, 2025)
This study discusses legal issues related to the application of restorative justice in resolving child crime cases in Bengkulu. Child crime cases are a serious problem because they involve violations of children's rights guaranteed by law. In practice, conventional law enforcement often only emphasizes the punishment aspect without considering the best interests of the child. The formulation of the problem in this study focuses on how the application of restorative justice principles can be applied in resolving child crime cases in Bengkulu and to what extent the family deliberation approach can be an effective solution in child legal protection. The research method used is normative juridical, with a statutory and conceptual approach through an analysis of relevant legal regulations and case studies of its application in the field. The results of the study indicate that the application of restorative justice through family deliberation provides a more humane, just, and oriented space for resolving relationships between perpetrators, victims, and families. This approach is considered effective in realizing child protection and prioritizing the principle of the best interests of children in accordance with the values ​​of social justice and humanity.